BONE TISSUE METABOLISM AND CHANGES IN THE ORAL CAVITY IN REDUCED FUNCTIONAL ACTIVITY OF THE THYROID GLAND: (literature review) - Skochylo, О. V.; Boitsanyuk, S. I.; Tverdokhlib, N. O. (International Journal of Medicine and Medical Research, 2022)
Background. Decreased functional activity of the thyroid gland leaves affects many organs and systems as well as bone tissue, pathological changes of which in the oral cavity are most often observed in periodontitis. However, the relationship between thyroid hypofunction and periodontitis or other inflammatory diseases of the oral cavity is still not confirmed. Objective. The aim of the review was to study the published information and analyse bone metabolism and its relationships between autoimmune thyroiditis and oral diseases. Methods. The articles in foreign periodicals on endocrinology, pathophysiology, dental surgery and therapy were the scientific sources for research. Results. Understanding the mechanisms of bone metabolism under the action of thyroid hormones is an important aspect of treatment and diagnostic process, as local treatment of dental pathology without reducing the impact on systemic factors ultimately does not have any positive result. Decreased functional activity of the thyroid gland leads to homeostasis imbalance in the body. The thyroid hormones are important for bone metabolism, publications on periodontitis incidence in cases of autoimmune pathology of the thyroid gland are the most common. However, despite the number of studies, most authors agree that they are currently insufficient to clearly establish a causal relationship between autoimmune thyroid disease and maxillofacial disorders. Conclusions. The study expands our knowledge, but there is still a need for further detailed studies that would clearly define the mechanisms of development of the disorders of the oral bone tissues and its relationships with autoimmune pathology of the thyroid gland.